Circulating Bacterial DNA: A New Paradigm for Cancer Diagnostics - Glyn, Tamara; Purcell, Rachel (Frontiers in Medicine, 2022)
Cell-free DNA applications for screening, diagnosis and treatment monitoring are increasingly being developed for a range of different cancers. While most of these applications investigate circulating tumour DNA (ctDNA) or methylation profiles of ctDNA, circulating bacterial DNA (cbDNA) has also been detected in plasma and serum samples from cancer patients. Recent publications have the detection of cbDNA in studies of breast, gastric, colorectal, hepatocellular and ovarian cancers. In several cases, distinction between patients and healthy controls was possible, based on cbDNA profiles, in addition to potential prognostic value. A large pan-cancer study demonstrated the feasibility of cbDNA to distinguish between four types of cancer and healthy controls, even in patients with early-stage disease. While improvements in, and standardisation of laboratory and bioinformatics analyses are needed, and the clinical relevance of cbDNA yet to be ascertained for each cancer type, cbDNA analysis presents an exciting prospect for future liquid biopsy screening and diagnostics in cancer.